PENGEMBANGAN MEDIA VIDEO TUTORIAL MATERI PENGOLAHAN TEKS DAN BENTUK PADA SOFTWARE COREL DRAW UNTUK MENINGKATKAN KEMAMPUAN MENCIPTA DI MATA PELAJARAN KOMPUTER GRAFIS KELAS XI DKV SMK MAHARDHIKA SURABAYA: bahasa Indonesia - Deva Lucya, Desvina; Mariono, Andi (Jurnal Mahasiswa Teknologi Pendidikan, 2026)
ABSTRACT Graphic Design learning in the Visual Communication Design (VCD) competency requires students to possess strong practical skills in operating vector-based graphic design software. However, differences in students initial abilities, limited learning resources, and low learning motivation often become obstacles in the learning process. This study aims to develop video tutorial media on Text and Shape Editing using CorelDRAW software and to determine its feasibility and effectiveness in improving students creative skills. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were Grade XI VCD students at SMK Mahardhika Surabaya. Data were analyzed using descriptive quantitative analysis and a paired sample t-test.The results showed that the developed video tutorial media was categorized as feasible based on expert validation and student trial results. The effectiveness test indicated an increase in the average posttest score compared to the pretest score, with a significant difference between students scores before and after using the video tutorial media. These findings prove that the video tutorial media is effective in improving students creative skills in producing digital poster designs using CorelDRAW software. Keywords: video tutorial media, CorelDRAW, ADDIE, creative skills, Visual Communication Design